Um recurso educacional teórico-prático para ensinar transformações dos materiais e elaborar avaliações para as crianças na perspectiva investigativa: atitudes e procedimentos, para além do conteúdo conceitual - Bárbara Maria Ribeiro Ferreira (2020)
This paper was developed through the analysis of data produced in the course for early grade teachers, with a total workload of 16 hours, at the Center for Science and Mathematics Teaching at the School of Education of the Federal University of Minas Gerais (CECIMIG/FaE/UFMG). The main motivator for its realization was the need to understand how to plan, teach, and evaluate the content of transformations of materials from an investigative perspective. We aimed to produce a theoretical and practical educational resource to teach transformations of materials and to elaborate assessments for the students. The result was based on the analysis of the data obtained through the questionnaire about the teachers' prior conceptions about the topics transformations of materials, assessment, and inquiry-based science teaching. In addition, we used data from the development of activities performed by them during the course, as well as the documentary analysis of a bank of questions and items already produced and used in assessments of elementary school I (2nd to 5th grade) in the period from 2016 to 2018, in a private school in Belo Horizonte. To perform the mentioned analyses, we used the assumptions of ATD (Textual Discourse Analysis), the theoretical frameworks of teaching by research, studies on transformations in the fundamental level (early years), teacher training and educational assessment.